2016
DOI: 10.1183/13993003.01796-2015
|View full text |Cite
|
Sign up to set email alerts
|

Hiatal hernia on thoracic computed tomography in pulmonary fibrosis

Abstract: Gastro-oesophageal reflux has long been suspected of implication in the genesis and progression of idiopathic pulmonary fibrosis (IPF). We hypothesised that hiatal hernia may be more frequent in IPF than in other interstitial lung disease (ILD), and that hiatal hernia may be associated with more severe clinical characteristics in IPF.We retrospectively compared the prevalence of hiatal hernia on computed tomographic (CT) scans in 79 patients with IPF and 103 patients with other ILD (17 scleroderma, 54 other co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 32 publications
4
31
0
4
Order By: Relevance
“…We found that hiatal hernia was both common and associated with baseline fibrosis score in SSc‐ILD, although there was no independent association of hiatal hernia with disease progression or mortality. The 21% hiatal hernia prevalence reported in our study was less than the 59% observed in a recent retrospective study of scleroderma patients and the 39–53% prevalence reported in IPF, and is more comparable to the prevalence previously observed in COPD (13%) and asthma (17%) . The reasons for these differences with other ILD cohorts are unclear.…”
Section: Discussionsupporting
confidence: 70%
“…We found that hiatal hernia was both common and associated with baseline fibrosis score in SSc‐ILD, although there was no independent association of hiatal hernia with disease progression or mortality. The 21% hiatal hernia prevalence reported in our study was less than the 59% observed in a recent retrospective study of scleroderma patients and the 39–53% prevalence reported in IPF, and is more comparable to the prevalence previously observed in COPD (13%) and asthma (17%) . The reasons for these differences with other ILD cohorts are unclear.…”
Section: Discussionsupporting
confidence: 70%
“…The association of GERD and pulmonary disease is a frequent one and certainly a causality association not a spurious relation. Several recent studies showed an increased prevalence of GERD in patients with asthma, pulmonary fibrosis, chronic cough and chronic obstructive pulmonary disease (COPD) (12,17,(49)(50)(51)(52) . GERD may damage the lung due to aspiration of gastric contents but pulmonary diseases may cause GERD due to changes in the TPG.…”
Section: • Pulmonary Diseases and Transdiaphragmatic Pressure Gradientmentioning
confidence: 99%
“…Asymptomatic GER and nonacid GER are also common in IPF [19,20 & ], complicating the manner in which GER is diagnosed and prevalence determined. In addition to GER, a large minority of patients with IPF also suffer from a hiatal hernia, which may exacerbate GER and further contribute to microaspiration [21,22].…”
Section: Gastroesophageal Reflux/hiatal Hernia Subgroupsmentioning
confidence: 99%